Budget deficit and economic growth in Namibia - Sakaria, Hilaria Ndilokelwa (Graduate School of Business (GSB), 2019)
The study provides an assessment of the relationship between budget deficit and economic growth in Namibia, using time series quarterly secondary data covering the period, 1990 to 2015. The study employed the Auto Regressive Distributed Lag (ARDL) Bounds Test and estimated the coefficients of the variables from the Error Correction Model in examining the relationship between budget deficit and economic growth. According to the cointegration test, the result has shown that past budget deficit and past Population growth has a negative and effect and that current Trade balance has a positive effect on economic growth in the short run. The overall findings indicate that budget deficit negatively affects economic growth. This is in conformity with the Neo-Classical Theory, which holds that fiscal deficit leads to low GDP. The study therefore recommends that government expenditure be invested in developmental infrastructure that will give positive results in the future.